Photocatalytic Behavior of Supported Copper Double Salt: The Role of Graphene Oxide. (12th May 2022) - Shabestari, Marjan E.; Baselga, Juan; Martin, Olga
Abstract : The design of a photocatalyst that may work efficiently with sunlight is a fundamental concern to fight against environmental pollution and electrochemical hydrogen storage devices. In this work, it has been found that the green microwave-assisted decoration of graphene by copper double salt (DS) enhances visible sunlight photocatalysis efficiency. Nanohybrids of graphene oxide decorated with Cu(I) and Cu(II) oxides and copper hydroxy nitrate double salt were selected as photocatalysts for the degradation of rhodamine B in aqueous solution to study the effect of the graphene oxide support. The photodegradation process followed a pseudo–first-order kinetics for the bare catalysts, but the supported catalysts were best fitted to the Langmuir-Hinshelwood model. Supported systems were more efficient in terms of turnover and apparent rate constants. Diffuse reflectance spectroscopy with the use of Kubelka-Munk function allowed to measure bandgap energies. It was found that the absorption edge was reduced about 30% for the supported systems.